2022
DOI: 10.21037/gs-22-701
|View full text |Cite
|
Sign up to set email alerts
|

Combined expression of the BRAFV600E mutation and PD-L1 in early papillary thyroid carcinoma and its relationship with clinicopathological features and recurrence—a retrospective cohort study

Abstract: Background: Identifying the high recurrence group of patients with early-stage papillary thyroid cancer (PTC) is the greatest challenge in the management of this disease. It has been noted that B-type Rafkinase (BRAF) V600E mutation and programmed death ligand 1 (PD-L1) are associated in PTC and highly expressed in PTC, correlating in PTC as potential prognostic biomarkers. However, whether they can be used to predict the aggressiveness and recurrence of early PTC remains unclear. Methods: Clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…It should be noted that in contrast to other studies ( 51 , 52 ), we did not find an association between positive ICS and the BRAF V600E mutation. A high frequency of BRAF V600E -positive RAI-R recurrent PTCs (approximately 70%) was found regardless of their ICS.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that in contrast to other studies ( 51 , 52 ), we did not find an association between positive ICS and the BRAF V600E mutation. A high frequency of BRAF V600E -positive RAI-R recurrent PTCs (approximately 70%) was found regardless of their ICS.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, this discrepancy is further compounded by the fact that many PTCs have BRAF mutations and also express CD274. 31 32 Therefore, we sought to investigate the significance of BRAF mutation and its downstream signaling on the expression of immune suppressive markers in PTC tissues. Further, we explore the efficacy of BRAF inhibitors in combination with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al found that PTC showed more malignant pathological features and early recurrence in patients with changes in internal environment (such as solid organ transplantation) ( 21 , 22 ). Beebeejaun et al speculated the interaction mechanism of PA and PTC in his article, high PTH level, Hypercalcemia and low 1,25 Dihydroxyvitamin D may lead to the growth and aggressivity of PTC ( 23 ).…”
Section: Discussionmentioning
confidence: 99%